Past and present of hepatitis E in the Netherlands. Issue 12 (29th May 2014) - Hogema, Boris M.; Molier, Michel; Slot, Ed; Zaaijer, Hans L.
<x xml:space="preserve">Abstract</x> Background Recent studies show that endemic hepatitis E virus (HEV) infection occurs frequently in some developed countries. In the Netherlands in 2013, the routine screening of 35, 220 plasma donations for HEV RNA showed 20 donors to be viremic (1:1761), which seems to contradict reports of declining HEV seroprevalence in the recent past. Study Design and Methods To asses HEV infection pressure changes over time, archived samples from Dutch blood donations collected in 1988 and 2000 were tested for anti‐HEV immunoglobulin (Ig)G. The findings were compared to the HEV seroprevalence among donors in 2011. Results The age‐adjusted prevalence of anti‐HEV IgG for Dutch donors aged 18 to 64 declined from 46.6% in 1988 to 27.3% in 2000 and to 20.9% in 2011. The reduction of seroprevalence was apparent for all age groups between 1988 and 2000, and for donors older than 40 between 2000 and 2011, but the seroprevalence among donors aged 18 to 29 increased between 2000 and 2011. Recent changes in HEV infection pressure are more apparent in the youngest donors, who to a lesser extent reflect cumulative exposure to HEV in the past. Donors aged 18 to 21 showed decreasing HEV seroprevalence from 19.8% in 1988 to 7.0% in 1995 and to 4.3% in 2000, followed by an increase to 12.7% in 2011. Conclusion HEV antibody patterns in young and old Dutch donors, in 1988 to 2011, suggest that decades ago, HEV was ubiquitous and most persons acquired infection. Subsequently HEV incidence was low during a prolonged period, to increase again in recent years.